Unsteady stagnation point flow of a non-Newtonian second-grade fluid - F. Labropulu; X. Xu; M. Chinichian (International Journal of Mathematics and Mathematical Sciences)
The unsteady two-dimensional flow of a viscoelastic second-grade fluid impinging on an infinite plate is considered. The plate is making harmonic oscillations in its own plane. A finite difference technique is employed and solutions for small and large frequencies of the oscillations are obtained.